Relevance of developing public health service cadres alongside a more prevention oriented Indian health system: an overview - Talukdar, Rounik (International Journal Of Community Medicine And Public Health, 2021)
The relevance of public health has been emphasized in the wake of the global epidemic COVID-19. There are several success stories that we often tend to forget, such as the fight against various infectious illnesses like smallpox, poliomyelitis, and current human-immunodeficiency virus (HIV) prevention, to name a few, public health has played a significant impact. Diarrheal diseases, for example, which contributes significantly to India's under-five mortality rate and is one of the leading causes of malnutrition, can be effectively handled by improving access to safe water and sanitation. Because public health encompasses more than just health, we require a workforce with managerial and leadership skills as well as training in public health as a specialty. This paper explores some of the successes and lessons learned from systematic investments in public health in the Indian state of Tamil Nadu, namely The Tamil Nadu model and other countries, as well as the system's flaws. In India, a feasible framework for establishing dedicated public health cadres has also been explored. Evidence was acquired from PubMed, Google Scholar, newspaper stories, and publicly released government orders and papers. The recruitment of cadres may resemble that of the Indian economic/statistical services (IES/ ISS) by the UPSC. Another area to emphasize for health professionals interested in public health is training. Starting from frontline workers, block level workers to district and state we need dedicated public health workforce. Moreover, the need of the hour is to establish such a system which will work alongside pre-existing clinical fields.